La literatura en juego - Valentina Litvan (Cuadernos LIRICO)
This article examines the transformation of Levrero’s literary discourse from an aesthetic crisis that began with the novela luminosa (the Luminous Novel) and intensifies with Diario de un canalla (Diary of a Scoundrel) and which finally reaches its most radical expression in Discurso vacío (The Empty Speech). In these three texts, Levrero challenges his own writing to the point of putting literature itself at stake. Confronted by the threat of a “spiritual death,” he declares his need to rescue the daimon or spirit in order to recover the keys of his own literature. However, given an impossible task, writing becomes a simple gesture. The empty form of an exercise whose sole grip is calligraphy. Writing stops being representation (fiction), nor is it conceptual (meta-literature) but rather a performative act of “self-construction”. Only the unconscious’ irruption through the discourse’s interruptions, as conveyed, for examply, by Pajarito’s apparitions (in Diario de un canalla) or Pongo, the dog, (in Discurso vacío) does he finally offer a foundation for literature.